The Role of Islamic Economics in Promoting Sustainable Economic Growth in Developing Countries : Systematic Literature Review (SLR) - Abiyajid Bustami; Rizky Awaliyah Maulidina (Journal of Business Management and Islamic Banking, 2025)
Research Aims: This study aims to identify, analyze, and synthesize findings from existing literature on the role of Islamic economics in promoting sustainable economic growth in developing countries. Methodology: Utilizing a Systematic Literature Review (SLR) approach, this study collects and evaluates data from scholarly books, journals, and academic research published between 2016 and 2024. The review follows a structured protocol, including clearly defined inclusion and exclusion criteria and rigorous study quality assessments. Research Findings: The results reveal that Islamic economics, particularly through sectors such as Islamic banking, sukuk, and the halal industry, significantly contributes to economic inclusivity, equitable wealth distribution, and environmental preservation. Originality: The  grand  theory  used  in  this  research the role of Islamic economics in supporting sustainable development in developing countries through economic inclusiveness and environmental preservation. Research limitation and implication: The limitation of this study lies in its reliance on literature without empirical data. Its implication specifically suggests that policymakers in developing countries should integrate Islamic economic principles such as profit-sharing, ethical investment, and environmental stewardship into national development strategies to achieve inclusive and sustainable growth.